Congenital lobar emphysema: Is surgery routinely necessary? - Bulut Ismet; Sunam Guven; Altuntas Bayram; Ceran Sami (Wolters Kluwer Medknow Publications, 2010)
Congenital lobar emphysema (CLE) is a rare congenital abnormality characterised by overinflation of a pulmonary lobe. Its aetiology is unknown. The management of CLE has traditionally been surgical. A newborn boy with a birthweight of 2.5 kg was delivered at full-term by caesarian section due to food delivery. There was no marked respiratory distress at birth, and little meconium stained liquor was seen on the skin. The initial diagnosis was meconium aspiration syndrome. After computed tomography of the thorax, CLE was diagnosed. The patient was observed throughout for a week and the CT of the thorax was repeated, which revealed that the emphysema had resolved. The nonoperative approach should be considered in asymptomatic patients with CLE.